Dispossession or Adaptation? Migration and Persistence of the Red River Metis, 1835‑1890 - Ens, Gerhard (Historical Papers / Communications historiques, 1988)
AbstractThe period from 1870 to 1890 saw the widespread dispersal of the Red River Metis. Inthe past historians have attributed this migration either to the inability of the Metis toadjust to settled society, or to the forced dispossession by the Canadian government.Both these views have some validity, but oversimplify the causes of the Metis emigrationfrom Red River. An examination of the changing nature of the Metis family economyand the dynamics of migration show that the Metis movement out of Red River hadbegun well before 1870 and was a response to new economic opportunities. Changes inthe Metis economy after 1850, changes that integrated the Red River Settlement into awider capitalist economy, also divided Metis society on economic and occupational linesand affected the decision whether to emigrate or not. Thus the dispersal of the Metis wasin some sense an adaptive and innovative response, one that had a different effect on thevarious Metis groups.